2020
DOI: 10.1007/s12229-020-09223-1
|View full text |Cite
|
Sign up to set email alerts
|

Paleorecords of Domesticated and Wild Grapevine in Romania: a Review

Abstract: This paper reviews the, so far available, paleorecords of Vitis sylvestris C.C. Gmel and Vitis vinifera L. from Romania. The study takes into consideration the presence of Vitis pollen from Holocene peat sediment sequences and archaeological context, but also the presence of macrorests from various archaeological sites that date from Neolithic, Chalcolithic, Bronze Age, and La Tène. Both paleobotanical arguments and archaeological discoveries support the theory that places the beggining of viticulture in Roman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 67 publications
(79 reference statements)
4
4
0
Order By: Relevance
“…The raisin and table grapevines (South African and European) had a moderate plant height compared to the wild and wine grapevines ( Figure 2 ). The result of the present study is in line with [ 13 , 14 ], that clearly and concisely reported that wild grapevines were vigorous compared to the modern grapes. This might be mainly due to genetic differences among the grapevine cultivars [ 15 ], sunlight distribution [ 9 ], and poor canopy management [ 16 ].…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The raisin and table grapevines (South African and European) had a moderate plant height compared to the wild and wine grapevines ( Figure 2 ). The result of the present study is in line with [ 13 , 14 ], that clearly and concisely reported that wild grapevines were vigorous compared to the modern grapes. This might be mainly due to genetic differences among the grapevine cultivars [ 15 ], sunlight distribution [ 9 ], and poor canopy management [ 16 ].…”
Section: Resultssupporting
confidence: 92%
“…The raisin and table grapevines had higher tendril number compared to the wine grapevines but lower than the wild grapevine cultivars ( Figure 12 ). Similar research findings were reported by [ 13 15 ] who found significant tendril number differences among grapevine cultivars. This might be due to genetic variations [ 15 ], vigorous nature of the vine [ 13 ], temperature [ 7 ], sunlight distribution [ 9 ], and canopy management [ 16 ].…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations